Response to COVID-19 in Europe and Central Asia : Policy and Practice Recommendations - Shmis, Tigran (World Bank, Washington, DC, 2020)
The Europe and Central Asia (ECA) Education Team's vision is for education systems to empower all to reach their full potential. In line with this vision, the purpose of this guidance note is to provide recommendations and policy advice for decision-makers on potential education responses to the COVID-19 crisis. The note includes measures for mitigating learning losses and preparedness for school re-openings and/or a second wave based on the following scenarios: (i) schools remain closed until the end of June and reopen in July allowing for the possibility of summer school; and (ii) schools remain closed through the summer, reopening for the next school year but with protracted disruptions.